VEGETATION SUCCESSION DYNAMICS STUDIES IN MOUNTAIN AREAS AFFECTED ERUPTION API Kelud REMOTE SENSING DATA BASED ON THE YEAR 2013 - 2016 - Nuzulah, Siti Nurin; -, Purwanto -; Bachri, Syamsul - (Media Komunikasi Geografi, 2016)
Investigate of this research shows that on January 4th 2014 vegetation density in Impact Eruption Area of Kelud Volcano 10 km has vegetation index value 0,64 – 0,34. On February 17th, 2014 the vegetation succession dynamic happens a decreasing vegetation succession dynamics with vegetation index value between 0,52 – 0,01. In 2014 towards 2015 there was an increase vegetation succession with vegetation index values between 0,87 – 0,1. On wet dry month 2015 towards a decline in vegetation succession dynamics caused by the influence of the dry season with vegetation index values between 0,7 – 0,06. In 2016 there was an increase in wet secondary vegetation succession in the Sumberasri village Ngleggok district is the climax of the process of succession with vegetation index values 0,89. The dynamics of vegetation succession have not run optimally on a five kilometer radius with vegetation index value 0,1 in Sugihwaras village Ngancar District. Perhutani can support of temperature constant at 5 km by planting a plant hard. The kinds of this plant hard is Kaliandra dan Pines that can to plant in coordinate 49 M 0641939 9123036. Constant temperature will support the condition of succession vegetation until in condition before happen an eruption by referral addiction 0,24 vegetation index.Keywords: succession, vegetation, eruption, remote sensing.